Phenolic Compound Profiles, Cytotoxic, Antioxidant, Antimicrobial Potentials and Molecular Docking Studies of Astragalus gymnolobus Methanolic Extracts - Esra Aydemir; Elif Odabaş Köse; Mustafa Yavuz; A. Cansu Kilit; Alaaddin Korkut; Serap Özkaya Gül; Cengiz Sarikurkcu; Mehmet Engin Celep; R. Süleyman Göktürk (Plants, 2024)
Since Astragalus is a genus with many important medicinal plant species, the present work aimed to investigate the phytochemical composition and some biological activities of Astragalus gymnolobus. The methanolic fractions of four organs (stems, flowers, leaves, root and whole plant) were quantified and identified by Liquid Chromatography Electrospray Ionization Tandem Mass Spectrometry (LC–ESI–MS/MS) analysis. Hesperidin, hyperoside, p-hydroxybenzoic acid, protocatechuic acid and p-coumaric acid were identified as main compounds among the extracts. Among all cells, leaf methanol (Lm) extract had the highest cytotoxic effect on HeLa cells (IC50 = 0.069 μg/mL). Hesperidin, the most abundant compound in A. gymnolobus extract, was found to show a strong negative correlation with the cytotoxic effect observed in HeLa cells according to Pearson correlation test results and to have the best binding affinity to targeted proteins by docking studies. The antimicrobial activity results indicated that the most susceptible bacterium against all extracts was identified as Streptococcus pyogenes with 9–11 mm inhibition zone and 8192 mg/mL MIC value. As a result of the research, it was suggested that A. gymnolobus could be considered as a promising source that contributes to the fight against cancer.